IBN KHALDUN’S THEORY OF ASABIYYAH AND THE CONCEPT OF MUSLIM UMMAH - Ab Halim, Asyiqin (Journal of Al-Tamaddun, 2014)
Theory of Aṣabiyyah as introduced by Ibn Khaldūn is concerning notion of sharing common descent and sense within particular group members. It is natural feelings of affection instilled in human beings, mainly in protecting their group members or brothers who are treated unjustly. Hence, it is depicted in line and not contrary to Islam based on this basis. However, within Islam, there is a concept of Muslim Ummah which based on faith and respect and notion of universal brotherhood, regardless ethnic or group background. Hence, this paper examines whether the theory of Aṣabiyyah fit into the concept of Muslim Ummah or not, and the similarities and differences between these two concepts. In other words, this paper discusses further the comparison between Ibn Khaldūn theory of Aṣabiyyah and the concept of Muslim Ummah, as well as examine the theory of Aṣabiyyah from the Islamic perspective.